Amblyopia Revisited: Putting The Theoretical Knowledge To Practical Use - Sahil Panjwani; Amritjeet Kaur (Delhi Journal of Ophthalmology)
Amblyopia is one of the most common causes of vision loss in childhood. Conventionally, amblyopia has been considered as a unilateral visual diminution and hence, most definitions fail to describe the visual acuity in defining bilateral amblyopia. The mainstay of treatment consists of occluding the sound eye with patches. Choosing the appropriate duration of patching remains a source of confusion for many clinicians. There are also greatly varied opinions when it comes to deciding the upper limit of age for which patching is effective. Many clinical trials have been performed to answer these questions. This article aims to review the current literature regarding the amblyopia definition and treatment strategies to guide the clinician in diagnoses and management of amblyopia more confidently.